Study of STAT3 Expression in Different Phases of Patients with Chronic Myeloid Leukemia - Peyman Yousefi; Shahrbano Rostami; Nasrin Alizadeh Ghandfurosh; Saeed Mohammadi; Mohsen Nikbakht; Laya Ghadyaninejhad; Bahram Chahardouli (Tehran University of Medical Sciences, 2019)
Background and Aim: Chronic myeloid leukemia(CML) is a clonal myeloproliferative disease, characterized by BCR/ABL translocation. Using tyrosine kinase inhibitors such as Imatinib, treatment for this disease has progressed remarkably. However, resistance to tyrosine kinase inhibitor is a major obstacle. Signal transducer and activator of transcription 3(STAT3) is an important transcription factor in proliferation and survival of several cancers. The aim of this study was to determine the expression of STAT3 and its role in drug resistant CML patients treated with Imatinib. Materials and Methods: Peripheral blood was collected from 71 CML patients in different phases of the disease and 10 healthy individuals. After extracting RNA and synthesizing cDNA, expression of STAT3 gene was measured using Real-Time PCR technique. The expression of STAT3 was normalized to ABL control gene. Then expression levels were compared with the control group. Results: The results showed that expression of STAT3 in the diagnostic stage was significantly higher than healthy individuals(p=0.0001). STAT3 expression was not significantly different from MMR and the control group. STAT3 expression was significantly higher in non-mutated and mutated ABL kinase domain Imatinib resistant patients as compared to patitents in MMR stage (p=0.0014 & p=0.003). This difference was not significant between the two resistant groups. Blastic phase patients had no significant difference in the expression of STAT3 with the control group. Conclusion: Considering the results of this study and the role of STAT3 in cell proliferation and survival, the targeting of STAT3 seems to be an effective option in the treatment of resistant patients.